Effect of Emotional Intelligence on Academic Achievement of Senior Secondary School Students in Biology in Wukari Metropolis - Fadahunsi, John A.; Abdullahi, Abdulazee Hassan; Sunday, Adiele; Stephen, Mathew (Darul Yasin Al Sys, 2025)
This study investigates the effect of emotional intelligence on the academic achievement of senior secondary school students in Biology within Wukari Metropolis, Nigeria. Specifically, the study examines the influence of emotional awareness, emotional management, socio-emotional awareness, and relationship management on students’ academic performance. A descriptive research design was adopted, with a sample of 150 students selected through simple random sampling. Data were collected using a structured questionnaire and analyzed using mean and standard deviation. The findings reveal that emotional awareness significantly influences academic achievement in Biology, as students with higher emotional awareness tend to perform better academically. Additionally, students exhibited challenges in emotional management, which adversely impacted their academic performance. Socio-emotional awareness was also found to be a contributing factor, highlighting the importance of interpersonal understanding in academic contexts. Furthermore, relationship management skills, including help-seeking behavior and collaboration, positively influenced student achievement in Biology. The study concludes that emotional intelligence plays a vital role in academic success and recommends the integration of emotional intelligence training into the school curriculum. Such initiatives would support the development of self-awareness, emotional regulation, and interpersonal competencies, thereby fostering improved academic outcomes among secondary school students.